Prevention of infection and optimizing vaccination in the solid organ transplant candidate and recipient. Issue 4 (August 2021) - Ryu, HaYoung; Narayanan, Navaneeth; Bhatt, Pinki J.
Abstract : Purpose of review: Infections can result in serious complications in solid organ transplant (SOT) patients. The need to remain up to date on recommendations on screening, vaccinations, and chemoprophylaxis is paramount in the management of SOT patients. The goal of this review is to provide an overview of current recommendations for the prevention of infections and optimization of vaccinations from the pretransplant through posttransplant periods. Recent findings: There is an emphasis on thorough pretransplant evaluation to guide clinicians and pretransplant testing based on epidemiological and endemic risk factors. Additionally, recent studies on vaccine safety and efficacy of newer vaccine formulations in SOT recipients are addressed. Summary: This review provides insight on updated recommendations for pretransplant screening, new data on vaccine optimization in SOT recipients and posttransplant prophylaxis. Further research is needed in order to improve preventive measures including screening tests, vaccines, and chemoprophylaxis.